Preparation method of low-density steel, low-density steel, vehicle front anti-collision beam and vehicle
By performing Nb and Ti microalloying treatment and process optimization on high Mn and high Al low-density steel, the problems of grain refinement and κ phase precipitation in the preparation process are solved, and high strength, good formability and wide application of the material are achieved.
Patent Information
- Application Number
- CN202510412024.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-06-17
AI Technical Summary
During the preparation process, existing low-density steels have problems such as grain refinement difficulty, uneven precipitation of κ phase, insufficient forming properties and plastic toughness, which limits their widespread use in automotive applications.
By performing Nb and Ti microalloying treatment on high Mn and high Al low-density steels, combined with double-roll thin-band continuous casting, homogenization annealing, cold rolling and static recrystallization annealing, the formation of grains and κ phases is controlled to generate κ phases with fine dispersion distributions inside the grains.
The stability and strength of the isoaxial austenite grain structure of low-density steel is achieved, while the forming property and plastic toughness of the material are improved, and its application range in the car body is expanded.
Smart Images

Figure CN120155537A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of steel, and particularly to a preparation method of low-density steel, low-density steel, a vehicle front anti-collision beam and a vehicle. Background Art
[0002] At present, the main component system of low-density steel is Fe-Mn-Al-C. Its basic development idea is to add a certain amount of Al to Mn steel to reduce the density of the steel. The reasons for the decrease in the steel density are not only that the relative atomic mass of Al is much lower than that of Fe, but also that the addition of Al increases the lattice parameter of the alloy. According to calculations, adding 1 wt.% of Al to Mn steel can bring about a density decrease of about 1.3%. Since austenitic single-phase low-density steel will exhibit higher strength under impact load while keeping the elongation basically unchanged, it can become a powerful competing solution for hot-formed steel, etc. Therefore, it is necessary to increase the proportion of Mn content in low-density steel in order to prepare austenitic single-phase low-density steel.
[0003] In high-Mn high-Al low-density steel, the κ-phase finely and dispersedly distributed inside the grains is a very crucial strengthening phase, which can greatly improve the material strength while basically not affecting its elongation. Refining grains (fine grain strengthening) can effectively improve the strength of the material while improving plasticity and toughness. However, the process of refining grains may also bring new problems, such as the precipitation of larger lamellar κ-phase at grain boundaries, which will have a negative impact on the formability and plastic toughness of the material.
[0004] Therefore, there is an urgent need for a reasonable and relatively wide aging process control window to control the grains and κ-phase of high-Mn high-Al low-density steel. Summary of the Invention
[0005] The present application provides a preparation method of low-density steel, low-density steel, a vehicle front anti-collision beam and a vehicle, so as to control the grains and κ-phase of low-density steel by regulating the steel preparation process.
[0006] In a first aspect, the present application provides a preparation method of low-density steel, including:
[0007] Preparing the low-density steel alloy composition, wherein the low-density steel alloy composition includes Fe, Mn, Al, C, Nb, Ti;
[0008] Performing twin-roll strip casting on the melted low-density steel alloy composition to obtain a cast steel coil;
[0009] Performing homogenization annealing, cold rolling and static recrystallization annealing on the cast steel coil, wherein the homogenization annealing temperature is 1000°C - 1200°C, and the temperature of the static recrystallization annealing is 900°C - 1100°C;
[0010] The cast steel product after static recrystallization annealing is subjected to aging treatment to obtain a low-density steel coil, wherein the temperature of the aging treatment is 450°C - 650°C.
[0011] Optionally, the time of the recrystallization annealing is 20 minutes - 60 minutes;
[0012] And / or, the time of the homogenization annealing is 3 hours - 6 hours.
[0013] Optionally, the time of the aging treatment is 4 hours - 16 hours.
[0014] Optionally, the method further includes:
[0015] The cut low-density steel coil is subjected to induction heating through an electromagnetic induction device to obtain a heated low-density steel coil, wherein the heating temperature is 300°C - 500°C;
[0016] The heated low-density steel coil is transferred to a cold stamping or cold roll pressing device for forming parts to obtain low-density steel parts.
[0017] Optionally, the time for transferring the heated low-density steel coil to the cold stamping or cold roll pressing device is less than 10 seconds.
[0018] Optionally, the alternating current frequency of the electromagnetic induction device is 40 kHz - 100 kHz, and the interval between the coil and the cut low-density steel coil is 1.5 mm - 4 mm.
[0019] Optionally, the thickness of the cast steel coil after static recrystallization annealing is 0.8 mm - 1.6 mm.
[0020] In a second aspect, the present application also provides a low-density steel, which is prepared by the preparation method of the low-density steel according to any one of the first aspect.
[0021] Optionally, the grain size of the equiaxed austenite grain structure of the low-density steel is 5 μm - 80 μm.
[0022] Optionally, in the low-density steel, the mass content of Mn element is 25% - 35%, the mass content of Al element is 7% - 11%, the mass content of C element is 0.7% - 1.0%, the mass content of Nb is 0.03% - 0.1%, and the mass content of Ti is 0 - 0.1%.
[0023] In a third aspect, the present application provides a vehicle front anti-collision beam, which is made of the low-density steel according to any one of the second aspect.
[0024] In a fourth aspect, the present application provides a vehicle, which is made of the low-density steel according to any one of the first aspect.
[0025] The preparation method of low-density steel, low-density steel, vehicle front anti-collision beam and vehicle provided by this application involve microalloying treatment of high-Mn high-Al low-density steel with Nb and Ti, followed by twin-roll strip casting, homogenization annealing, cold rolling and static recrystallization annealing, and aging treatment. In terms of composition, since the binding force between Nb, Ti and C is very strong, it inhibits the spinodal decomposition of austenite, which helps to obtain a more stable austenite matrix at room temperature. At the same time, it inhibits the precipitation of large blocky lamellar κ-phase at grain boundaries in the fine-grained structure and reduces the size and volume fraction of intragranular κ-phase. It plays a good role in regulating the nucleation and precipitation position of κ-phase. Through temperature control in each step, the low-density steel generates κ-phase that meets the requirements during aging treatment, and fine and dispersed κ-phase is generated inside the grains. In addition, by combining the twin-roll strip casting technology with a sub-rapid cooling rate and the subsequent cold rolling technology, the casting problems of high-Mn high-Al low-density steel are reduced, and its plate thickness is decreased, thereby expanding the applicable range on the vehicle body. Description of the Drawings
[0026] The drawings herein are incorporated into the specification and form a part of this specification, showing embodiments consistent with this application, and are used together with the specification to explain the principles of this application.
[0027] Figure 1 Flow schematic of the preparation method of low-density steel provided by this application Figure 1 ;
[0028] Figure 2 Physical comparison diagram provided by this application.
[0029] Through the above drawings, specific embodiments of this application have been shown, and there will be more detailed descriptions hereinafter. These drawings and written descriptions are not intended to limit the scope of the concept of this application in any way, but to illustrate the concept of this application to those skilled in the art by referring to specific embodiments. Detailed Description of the Embodiments
[0030] Here, the exemplary embodiments will be described in detail, and the examples are shown in the drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. On the contrary, they are merely examples of devices and methods consistent with some aspects of this application as detailed in the appended claims.
[0031] With the continuous development of the automotive industry, promoting the extreme cost reduction and weight reduction of commercial vehicle products is a key measure to ensure their endurance and maintain product competitiveness. The application of new materials in vehicle models can often play an important role in achieving extreme cost reduction and weight reduction. Metal materials have an absolute application proportion in commercial vehicles, so high-strength lightweight metal materials such as high-strength steel and aluminum alloy have become the key development solutions for new vehicle materials.
[0032] However, the thinning of various high-strength steels has approached the limit, and the price of aluminum alloy is too high, resulting in the development of new metal materials gradually entering a bottleneck period.
[0033] The gradual maturity of high-strength, tough and low-density steel for automobiles provides a turning point for the above development dilemmas. At present, the main component system of low-density steel is Fe-Mn-Al-C. By adjusting the contents of Mn / Al / C and optimizing the deformation and heat treatment process parameters, it can be ensured that the low-density steel has mechanical properties basically equivalent to those of various high-strength steels such as DP steel, DH steel, girder steel, and hot-formed steel. Especially in automotive safety components, due to its higher strain hardening rate, austenitic single-phase low-density steel will exhibit higher strength while maintaining the elongation basically unchanged when subjected to impact loads, so it can become a powerful competitive solution for hot-formed steel, etc.
[0034] If all the high-strength steel on the vehicle model is replaced with low-density steel, a weight reduction of about 5%-15% can be achieved on the basis of keeping the shape and size of the existing parts unchanged. And the relatively high strength of low-density steel may also bring about a certain amount of structural weight reduction. However, to achieve large-scale substitution of low-density steel, there are still several key problems to be solved:
[0035] 1. Due to the addition of more Al and Mn, the casting process of low-density steel is more challenging and the material price is relatively higher;
[0036] 2. Facing low-density steels with different Al and Mn contents, it is necessary to specifically explore suitable deformation and heat treatment processes to fully exert their potential for thinning and mechanical properties, so as to expand their application scope in automobiles;
[0037] 3. The addition of more Mn and Al will lead to a significant increase in the strength of low-density steel, but it will also bring problems such as difficult part forming and serious springback;
[0038] 4. The welding performance of low-density steel is poor, resulting in low mechanical properties of its welded joints, which limits its application in safety components;
[0039] 5. The addition of more Al elements leads to a significant decrease in the elastic modulus of low-density steel, which is likely to cause insufficient stiffness of parts, thus limiting its thinning effect.
[0040] The above problems significantly restrict the application of low-density steel in automobiles. If the cost of vehicle models can be reduced by using low-density steel components while meeting the performance requirements, the resistance to promoting its application will be significantly reduced, thus accumulating experience and data on the batch preparation and application of low-density steel.
[0041] Based on the significant advantages and existing problems of low-density steel, the alternative development parts selected for vehicle models should meet the following conditions:
[0042] Condition 1: The price of the original component (raw material or mold) is relatively high, and there is at least the potential for cost reduction by replacing it with low-density steel;
[0043] Condition 2: It does not involve the welding process;
[0044] Condition 3: There is no high requirement for the stiffness of the component.
[0045] After screening, the height of the front anti-collision beam of the vehicle model meets the above conditions. First, in order to meet the export safety regulations, the front anti-collision beam of this vehicle model is prepared by using aluminum alloy extrusion profiles, and the price of the component is relatively high. Second, this component is a safety component, and the use of austenitic single-phase low-density steel can meet the relevant performance requirements. Third, the structure of this component is relatively simple and basically does not involve the welding process. Finally, this component is installed relatively independently inside the vehicle body and has few connections with other components, so the requirement for stiffness is relatively low.
[0046] In summary, the aluminum alloy front anti-collision beam is very suitable for alternative development research with low-density steel.
[0047] However, during the development of the low-density steel front anti-collision beam, several industrial practical problems still need to be solved:
[0048] Problem 1: Using a high-Mn and high-Al composition design to prepare austenitic single-phase low-density steel is a relatively feasible solution. However, there are many challenges in producing high-Mn and high-Al steel by traditional smelting production process routes. Due to the slow cooling rate, abnormally coarse dendrites will form in the solidification structure. When the Mn content exceeds 20 (wt.%), segregation is extremely likely to occur during solidification, resulting in compositional differences and affecting formability. When the Al content is greater than 1.5 (wt.%), the formed Al2O3 will react with the casting powder, suspend and aggregate, blocking the nozzle and affecting castability. In addition, the thinnest sheet prepared by the hot rolling production line capable of industrializing high-Mn and high-Al low-density steel is 2 mm, while most of the structural parts on the vehicle body are thin parts with a thickness of 0.8 - 1.6 mm. Therefore, the current hot rolling production line for low-density steel is difficult to provide sheets with sufficient weight reduction effect;
[0049] Problem 2: The high-Mn and high-Al austenitic single-phase low-density steel has a high strength. When using cold roll forming or cold stamping, the springback is serious, affecting the forming effect and production efficiency of the component. While using hot stamping, the die cost is too high, affecting the cost reduction effect;
[0050] Problem 3: In high-Mn high-Al low-density steel, the κ-phase that is finely and dispersedly distributed inside the grains through aging treatment is a very crucial strengthening phase, which can significantly improve the material strength while basically not affecting its elongation. However, the appropriate aging process window for this precipitated phase is very narrow. If the operation is slightly improper, large lamellar κ-phases are easily formed at the grain boundaries. Although this phase can still significantly improve the strength, it seriously damages the formability and plastic toughness of the material. Therefore, there is an urgent need for a reasonable and relatively wide aging process control window for the κ-phase;
[0051] Problem 4: Currently, there are no actual application cases of high-Mn high-Al low-density steel in the front anti-collision beam, and its structure needs to be optimized to ensure its service performance.
[0052] In view of the above problems, this application first designs the steel composition and conducts Nb and Ti microalloying treatment on high-Mn high-Al low-density steel. After the Nb and Ti composite microalloying treatment, it is easy to form high-temperature stable, dispersed, and fine nanoscale carbides with C. These carbides are distributed both inside and at the boundaries of high-temperature austenite grains. The carbides distributed at the grain boundaries will inhibit the growth of high-temperature austenite grains. The finer the grains, the better the strength and toughness of the steel usually are. Through aging treatment, a precipitated phase called the κ-phase is formed. The κ-phase is a nanoscale tiny phase that can be evenly distributed within austenite grains. It helps to improve the strength and hardness of the steel. In some cases, precipitated phases (such as the κ-phase) may aggregate at the grain boundaries of the steel to form larger lamellar precipitates, and such precipitates will cause grain boundary embrittlement and affect the toughness and mechanical properties of the steel. Through the Nb and Ti microalloying treatment, this situation can be avoided, so that the precipitated phase is evenly distributed inside the grains instead of forming large precipitates at the grain boundaries.
[0053] In addition, a method combining twin-roll strip casting technology with a sub-rapid cooling rate and cold rolling technology is adopted to reduce the casting blockage problem of high-Mn high-Al low-density steel and reduce its minimum sheet thickness to about 0.8 mm. When forming parts, the electromagnetic induction heating warm forming process of high-Mn high-Al low-density steel is used to improve the formability of the material and reduce the springback of the parts.
[0054] The following will specifically describe the technical solutions of this application and how the technical solutions of this application solve the above technical problems through specific embodiments. These specific embodiments below can be combined with each other, and the same or similar concepts or processes may not be repeated in some embodiments. The embodiments of this application will be described below in conjunction with the drawings.
[0055] Figure 1 Schematic flow of the preparation method of the low-density steel provided by this application Figure 1 as Figure 1As shown, the method includes the following steps:
[0056] S1. Prepare a low-density steel alloy composition, where the low-density steel alloy composition includes Fe, Mn, Al, C, Nb, and Ti.
[0057] Among them, the content of the Mn element is 25-35 (wt.%). When the Mn content exceeds 35%, the β-Mn phase will be formed, seriously damaging the formability and plasticity of the material. And the Mn element is a very crucial austenite stabilizing element. When it is lower than 25%, it is difficult to ensure the formation of a single-phase austenite structure. After homogenization annealing and quenching, the material will form a duplex structure with austenite as the matrix and a small amount of δ-ferrite phase, and the δ-ferrite will also seriously affect the plasticity of the material.
[0058] The content of the Al element is 7-11 (wt.%). The addition of a higher content of the Al element inhibits the TWIP effect and TRIP effect of austenitic steel, and planar slip of dislocations becomes its main deformation mechanism. At this time, the interaction between the main aging precipitation phase κ phase and planar slip dislocations in austenitic low-density steel is the key entry point for regulating the strength and toughness of the material. When the Al element is lower than 7%, it is difficult for the low-density steel to form the κ phase during aging, affecting the strengthening and toughening effect of the material. And when the Al content exceeds 11%, the excessive Al content will also promote the precipitation of large κ phases at grain boundaries, affecting the formability and plasticity of the material.
[0059] The content of the C element should be 0.7-1.0 (wt.%). If the C content is too low, the solution and aging strengthening effects of the material will be greatly reduced. If the content is too high, problems such as welding and anti-corrosion will occur.
[0060] The Nb content should be 0.03-0.1 (wt.%), and the Ti content should be 0-0.08 (wt.%). As strong carbide-forming elements, adding trace amounts of Nb and Ti to low-density steel can form extremely stable (Nb, Ti)C with C to stabilize and strengthen the austenite matrix. During deformation or high-temperature heat treatment, the extremely stable nanoscale precipitate (Nb, Ti)C can pin grain boundaries, inhibit the growth of austenite recrystallized grains, and at the same time enhance the strength of the austenite matrix by precipitation strengthening. At the same time, due to the strong binding force between Nb, Ti and C, it effectively consumes C atoms, inhibits the spinodal decomposition of austenite, and helps to obtain a more stable austenite matrix at room temperature. At the same time, the precipitation of the κ phase is inhibited, especially the precipitation of large lamellar κ phases at grain boundaries, and the size and volume fraction of the κ phase in the grains are reduced. It plays a very good role in regulating the nucleation and precipitation position of the κ phase. But when the Nb and Ti contents exceed 0.1%, the microalloying effect tends to saturate.
[0061] Therefore, the composition design of the high-Mn high-C austenitic low-density steel is Fe-(25-35)Mn-(7-11)Al-(0.7-1.0)C-(0.03-0.1)Nb-(0-0.1)Ti (wt.%).
[0062] S2. The alloy composition of the melted low-density steel is subjected to twin-roll strip casting to obtain a cast steel coil.
[0063] The temperature of the molten steel is maintained at 200 °C above the liquidus to ensure that the molten steel has an accurate alloy composition. Then, this molten steel is poured into the molten pool. The molten steel flows between the reversely rotating twin rolls. There is flowing cooling water inside both rolls to ensure that the molten steel rapidly solidifies within 0.5-1 s at a cooling rate of not less than 1000 K / s after contacting the roll surface, while being rolled into shape. The rolling force is 60 KN, and the casting speed is 0.5-1 m / s. To prevent oxidation, the molten pool and the casting and rolling system are both protected by N2. On the side of the molten pool, a ceramic baffle sintered from a mixed powder of BN and SiO2 that does not react with the melt is used for isolation and sealing. After the solidified cast strip leaves the roll, it is coiled. Its thickness is about 2 mm, and its width is about 200-400 mm. Through the twin-roll casting process, the degree of element segregation inside the steel can be significantly reduced, making it more convenient for homogenization annealing to eliminate element segregation, and the oxide inclusions are also significantly reduced.
[0064] However, the as-cast structure of the steel coil prepared by this process is very uneven. In the core part of the finally solidified cast strip, there is not only relatively serious micro-composition segregation, but also a central shrinkage cavity with a diameter of 10-40 μm is likely to form. Subsequent deformation and heat treatment are required to obtain a relatively uniform equiaxed grain structure.
[0065] S3. Homogenization annealing, cold rolling, and static recrystallization annealing are carried out on the cast steel coil. Among them, the homogenization annealing temperature is 1000 °C - 1200 °C, and the temperature of the static recrystallization annealing is 900 °C - 1100 °C.
[0066] In a specific implementation, the homogenization annealing temperature is 1000 °C, 1050 °C, 1100 °C, 1150 °C, 1200 °C, or a temperature range composed of any two of the above temperatures. The temperature of the static recrystallization annealing is 900 °C, 950 °C, 1000 °C, 1050 °C, 1100 °C, or a temperature range composed of any two of the above temperatures.
[0067] The homogenization annealing is kept warm for 3-6 h in the temperature range of 1100 °C - 1200 °C. To prevent oxidation on the surface of the cast steel coil, argon is used for protection during the heat preservation process, and air cooling quenching is carried out after the heat preservation ends.
[0068] The cast steel coil is rolled by a four-high cold rolling mill with a maximum rolling force of 6 MN. It is rolled for 2 - 5 passes, with a single-pass deformation of 10 - 20%, and there is no intermediate annealing. Finally, the steel coil is rolled into a sheet with a thickness of 0.8 - 1.6 mm, and the total deformation is 20% - 60%. After rolling, coiling treatment is carried out.
[0069] The cold-rolled sheet is subjected to recrystallization annealing treatment. The recrystallization annealing temperature is 900℃ - 1100℃, and the annealing time is 20 min - 60 min. To prevent oxidation and surface decarburization of the sheet, argon protection is carried out during the annealing process. If the annealing temperature is higher than 1100℃ or the annealing time is too long, the austenite grain will grow, and the fine grain effect will be severely affected. If the annealing temperature is lower than 900℃, κ-phase with various morphologies and different distribution positions is likely to form during annealing, affecting the plasticity and toughness of the material and the subsequent age hardening effect. After annealing, air cooling and quenching are carried out.
[0070] The nano-scale (Nb, Ti)C formed in the twin-roll continuous casting process remains stable in size and quantity during homogenization and static recrystallization annealing, and is evenly distributed inside and at the grain boundaries of austenite grains, playing an important role in inhibiting the growth of austenite recrystallized grains.
[0071] Controlling the temperature at 900℃ - 1100℃ and maintaining it for 20 min - 60 min will not produce abnormal κ-phase. During subsequent aging treatment, κ-phase of the generated temperature will be formed. If the temperature is too high, too low, or the annealing time is too long, unexpected κ-phase will be generated in this step, affecting the material properties.
[0072] S4. The cast steel product after static recrystallization annealing is subjected to aging treatment to obtain a low-density steel coil. Among them, the aging treatment temperature is 450℃ - 650℃.
[0073] The recrystallized steel coil is aged at a temperature of 450 - 650℃ for a holding time of 4 - 16 h. Argon protection is carried out during the holding process, and air cooling and quenching are carried out after aging. Uniform κ-phase is generated inside the material. If the aging temperature exceeds 650℃, the κ-phase is extremely likely to coarsen and form large-size lamellar precipitates at the grain boundaries, severely deteriorating the material properties. Below 450℃, the κ-phase is not easily precipitated. The addition of Nb and Ti microalloying elements plays a role in expanding the aging temperature range and inhibiting the formation of lamellar κ-phase at the grain boundaries. The aging temperature and time also have an important impact on the size, distribution, etc. of the κ-phase.
[0074] The low-density steel prepared by the method for preparing low-density steel of the present application is obtained by subjecting a high-Mn high-Al low-density steel to Nb and Ti microalloying treatment, followed by twin-roll strip casting, homogenization annealing, cold rolling, and static recrystallization annealing, and aging treatment. Through temperature control in each step, κ-phase that meets the requirements is generated during the aging treatment of the low-density steel, and fine and dispersed κ-phase is generated inside the grains. In addition, the molten steel after melting flows between two reversely rotating rolls. Cooling water flows through both of the two rolls to ensure that the molten steel rapidly solidifies within 0.5 - 1 s at a cooling rate of not less than 1000 K / s after contacting the roll surface, and at the same time, rolling forming is carried out. By means of this twin-roll strip casting technology and cold rolling technology with a sub-rapid cooling rate, the casting problems of high-Mn high-Al low-density steel are reduced, its plate thickness is decreased, thereby expanding the applicable range on the vehicle body.
[0075] The grain size of the equiaxed austenite grain structure of the low-density steel prepared by the above process method is 5 μm - 80 μm.
[0076] On the basis of the above embodiments, the coiled low-density steel after aging is transported to the component forming production line and cut. After the cut rolled plate is flattened, it is transported one by one in a pipeline form to an electromagnetic induction device for rapid induction heating. The electromagnetic induction device mainly consists of a pair of induction coils parallel to the rolled plate distributed above and below the pipeline, and the length of the induction coils is not less than the width of the rolled plate. Only the part of the rolled plate passing through the electromagnetic induction heating device will be instantaneously heated. Since the rolled plate quickly passes through the pipeline, the temperature difference of the whole plate can be ensured not to exceed 5°C. The heating induction coils are connected to a high-frequency current, and the alternating current frequency is 40 kHz - 100 kHz (specifically, it can be set to 50 kHz, 60 kHz, 70 kHz, 80 kHz, 90 kHz, 100 kHz, or the range composed of any two of the above), and the interval between the coil and the rolling flat plate is 1.5 mm - 4 mm. After the rolled plate is heated to 300 - 500°C, it is immediately transferred to a cold stamping or cold roll pressing device for warm forming, the transfer time does not exceed 10 s, and the maximum thinning rate of forming does not exceed 10%. After the components are formed, they are air-cooled to room temperature. After testing, the yield strength of the components reaches more than 900 MPa, the tensile strength reaches more than 1050 MPa, and the elongation rate reaches more than 30%. After an impact load, the tensile strength of the material reaches more than 2000 MPa, and the elongation rate remains above 25%.
[0077] Table 1 shows the mechanical property data of components prepared by electromagnetic induction heating and the same components prepared by hot forming.
[0078]
[0079] According to the data in Table 1, it can be determined that the low-density steel components prepared by the electromagnetic induction heating warm forming process have a strength close to that of hot-formed steel and a higher elongation. After impact loading, the tensile strength of the low-density steel formed by electromagnetic induction heating increases significantly while maintaining a high elongation.
[0080] Figure 2 The physical comparison diagram provided for this application shows that Figure 2 compared with the Q355 steel U-shaped parts prepared by cold stamping forming (the parts with a bright white surface), the low-density steel U-shaped parts prepared by the electromagnetic induction heating warm stamping process (the parts with a black-gray surface) fit more closely to the lower die, and the springback of the parts is smaller.
[0081] Electromagnetic induction heating can quickly and uniformly heat the local area of the rolled plate, heating the material to a temperature range of 300 - 500 °C. In this temperature range, the plasticity of the low-density steel is significantly improved, making it easier for the material to undergo plastic flow during the forming process. The higher temperature reduces the yield strength of the material and increases its ductility, thus making the deformation of the material during the forming process smoother and reducing possible cracks or other forming defects during the forming process.
[0082] Since electromagnetic induction heating is fast and local, it can ensure that the temperature difference during the heating process does not exceed 5 °C. This means uniform heating, avoiding non-uniform material properties caused by too high or too low temperatures, and further improving the formability of the material. This uniform heating avoids temperature non-uniformity in different regions of the material, thus reducing the forming difficulty caused by material hardness differences.
[0083] During the warm forming process, due to the appropriate temperature of the material, it will not produce excessive elastic deformation like in the normal temperature state when subjected to external forces. When the temperature is higher, the springback coefficient of the material is lower and the yield strength decreases, making the deformation more stable. Therefore, after forming, the springback phenomenon of the parts is effectively reduced and the accuracy after forming is higher. After electromagnetic induction heating, the rolled plate can be transferred to cold stamping or cold roll pressing equipment for forming within just 10 seconds. This rapid heating and transfer helps to maintain the good plastic state of the material, enabling it to better adapt to the die shape during the forming process and reducing the springback risk.
[0084] The low-density steel prepared above is made into the front anti-collision beam of a vehicle. The structural design of the front anti-collision beam made of high-Mn high-Al low-density steel is carried out. The steel front anti-collision beam mainly includes the anti-collision beam body, the inner and outer plates of the left and right energy-absorbing boxes, the rear connecting plates of the energy-absorbing boxes, and connecting parts such as bolts and nuts. The anti-collision beam body is designed to be approximately "U"-shaped or "C"-shaped, with a plate thickness of 1.4 - 1.6 mm. The size of the formed anti-collision beam body is 1157 (length) * 161 (width) * 47 (depth), and the calculated total weight (calculated according to the normal density of Fe, 7.8 g / cm3, the same below) is about 2.92 kg - 3.34 kg. The energy-absorbing box is a square structure including the inner and outer plates, with a thickness of 1.3 - 1.5 mm, and the total weight of a single energy-absorbing box is about 0.38 kg - 0.47 kg. There are 2 rear connecting plates of the energy-absorbing boxes, with a thickness of 2.6 - 3 mm, and the weight of a single plate is 0.64 kg - 0.74 kg. If the connecting parts are not included, the total weight of the steel front anti-collision beam assembly is 4.972 kg - 6.67 kg. According to the digital model data of the aluminum alloy cavity extrusion profile of the LCV export vehicle model, the weight of its front anti-collision beam assembly (excluding the connecting parts) is 5.77 kg. Considering that the low-density steel will bring a weight reduction of 8 - 13%, the minimum weight of the front anti-collision beam assembly made of high-Mn high-Al low-density steel is 4.32 kg, and the maximum is only 6.13 kg, and the latter is only slightly higher than the front anti-collision beam made of aluminum alloy extrusion profile. Through the CAE simulation results, it can be seen that even if all the above-mentioned thinnest plate design schemes are selected, the prepared low-density steel front anti-collision beam can still meet the collision safety requirements. Therefore, using the low-density steel front anti-collision beam has an obvious weight reduction effect compared with the aluminum alloy anti-collision beam, with a maximum weight reduction of 25%. Cold stamping die design and development are carried out for each component of the low-density steel front anti-collision beam.
[0085] Specific example
[0086] Step 1: Prepare the alloy composition of high-Mn high-Al low-density steel, and its composition is Fe-30Mn-10Al-1.0C-0.05Nb-0.05Ti (wt.%).
[0087] Step 2: Carry out medium-frequency vacuum induction furnace melting and twin-roll strip continuous casting on the low-density steel in Step 1.
[0088] Pour the molten steel with precise alloy composition at a temperature above the liquidus of 200 °C into the molten pool, and then let it flow between two reversely rotating twin rolls. There is flowing cooling water inside both rolls to ensure that the molten steel rapidly solidifies within 0.6 s at a cooling rate of 1100 K / s after contacting the roll surface, while being rolled into shape. The rolling force is 60 kN, and the casting speed is 0.8 m / s. To prevent oxidation, both the molten pool and the casting and rolling system are protected by N2. On the side of the molten pool, a ceramic baffle sintered from a mixed powder of BN and SiO2 that does not react with the melt is used for isolation and sealing. After the solidified cast strip leaves the rolls, it is coiled. Its thickness is about 2 mm, and its width is about 300 mm.
[0089] Step 3: Perform homogenization annealing, cold rolling, and static recrystallization annealing on the cast steel coil prepared in Step 2.
[0090] The homogenization annealing process is to hold at 1150 °C for 4 h. To prevent oxidation on the surface of the cast steel coil, argon is used for protection during the holding process, and air cooling quenching is carried out after the holding ends. A four-high cold rolling mill is used to roll the cast steel coil, and the maximum rolling force is 6 MN. A total of 2 passes are rolled, with a single-pass deformation of 15%, without intermediate annealing. Finally, the steel coil is rolled into a sheet with a thickness of 1.445 mm, and coiling treatment is carried out after rolling. The cold-rolled sheet is subjected to recrystallization annealing treatment. The annealing temperature is 1000 °C, and the annealing time is 30 min. To prevent oxidation and surface decarburization of the sheet, argon protection is carried out during the annealing process. Finally, an equiaxed austenite grain structure with an average grain size of about 28 μm is obtained.
[0091] Step 4: Perform aging treatment on the steel coil after static recrystallization in Step 3.
[0092] The steel coil after recrystallization is aged at a temperature of 550 °C for 10 h. Argon is used for protection during the holding process, and air cooling quenching is carried out after aging.
[0093] Step 5: Conduct structural design on the front anti-collision beam of high-Mn high-Al low-density steel.
[0094] The steel front anti-collision beam mainly includes the anti-collision beam body, left and right
[0095] The inner and outer plates of the energy-absorbing box, the rear connecting plate of the energy-absorbing box, and connecting parts such as bolts and nuts. The anti-collision beam body is designed in an approximate "U" shape, with a plate thickness of about 1.4 mm. After forming, the size of the anti-collision beam body is 1157 (length) * 161 (width) * 47 (depth), and the calculated total weight (calculated according to the normal density of Fe, 7.8 g / cm3, the same below) is about 2.92 kg. The energy-absorbing box is a square structure including inner and outer plates, with a thickness of about 1.4 mm, and the total weight of a single energy-absorbing box is about 0.40 kg. There are 2 rear connecting plates of the energy-absorbing box, with a thickness of 2.6 - 3 mm, and the weight of a single plate is 0.68 kg. If the connecting parts are not included, the weight of the steel front anti-collision beam assembly is 5.08 kg. And because 10% of Al is added to the low-density steel, it can continue to bring about 13% weight reduction, and the weight of the low-density steel front anti-collision beam is about 4.42 kg. It reduces the weight by about 23% compared with the aluminum alloy extruded profile front anti-collision beam. Corresponding cold stamping die designs and developments are carried out for each component of the low-density steel front anti-collision beam.
[0096] Step 6: Transport the aged low-density steel coil to the component forming production line and cut it. After the cut rolled plate is flattened, it is transported to the electromagnetic induction equipment one by one in a pipeline form for rapid induction heating.
[0097] The heating induction coil is connected to a high-frequency current, the alternating current frequency is 90 kHz, and the distance between the coil and the rolled flat plate is 2 mm. After the rolled plate is heated to 500 °C, it is immediately transferred to cold stamping or cold roll pressing equipment for warm forming, and the transfer time does not exceed 10 s, and the maximum thinning rate during forming does not exceed 8%. After the components are formed, they are air-cooled to room temperature. After testing, the yield strength of the components reaches 930 MPa, the tensile strength reaches 1100 MPa, and the elongation rate reaches 32%. After the impact load, the tensile strength of the material reaches 2100 MPa, and the elongation rate is 27%.
[0098] This application provides a low-density steel, which is prepared by the above-mentioned preparation method of low-density steel.
[0099] Optionally, the grain size of the equiaxed austenite grain structure of the low-density steel is 5 μm - 80 μm.
[0100] This application also provides a vehicle front anti-collision beam, which is made of the low-density steel prepared by the above-mentioned preparation method of low-density steel, and then the vehicle front anti-collision beam produced.
[0101] This application also provides a vehicle, which is made of the low-density steel prepared by the above-mentioned preparation method of low-density steel, and then the vehicle is manufactured with the vehicle components produced.
[0102] Finally, it should be noted that those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses, or adaptations of the present invention, which follow the general principles of the present invention and include well-known common general knowledge or conventional technical means in the technical field not disclosed in the present invention. It is not limited to the exact structures described above and shown in the drawings, and various modifications and changes can be made without departing from its scope. The scope of the present invention is only limited by the appended claims.
Claims
1. A method for preparing low-density steel, characterized in that: include: Preparing a low-density steel alloy composition, wherein the low-density steel alloy composition includes Fe, Mn, Al, C, Nb, and Ti; Performing twin-roller thin strip continuous casting on the smelted low-density steel alloy component to obtain a cast steel coil; The cast steel coil is subjected to homogenization annealing, cold rolling and static recrystallization annealing, wherein the homogenization annealing temperature is 1000° C.-1200° C., and the static recrystallization annealing temperature is 900° C.-1100° C.; The cast steel product after static recrystallization annealing is subjected to aging treatment to obtain a low-density steel coil, wherein the aging treatment temperature is 450°C-650°C.
2. The method according to claim 1, characterized in that The recrystallization annealing time is 20 minutes to 60 minutes; And / or, the homogenization annealing time is 3 hours to 6 hours.
3. The method according to claim 1, characterized in that The aging treatment time is 4 hours to 16 hours.
4. The method according to any one of claims 1 to 3, characterized in that: The method further comprises: The cut low-density steel coil is subjected to induction heating by an electromagnetic induction device to obtain a heated low-density steel coil, wherein the heating temperature is 300° C.-500° C.; The heated low-density steel coil is transferred to a cold stamping or cold rolling device for component forming to obtain a low-density steel component.
5. The method according to claim 4, characterized in that The time for transferring the heated low-density steel coil to the cold stamping or cold rolling equipment is less than 10 seconds.
6. The method according to claim 4, characterized in that The alternating current frequency of the electromagnetic induction device is 40kHz-100kHz, and the interval between the coil and the cut low-density steel coil is 1.5mm-4mm.
7. The method according to any one of claims 1 to 3, characterized in that: The thickness of the cast steel coil after static recrystallization annealing is 0.8 mm to 1.6 mm.
8. A low-density steel, characterized in that: The low-density steel is prepared by the method for preparing low-density steel according to any one of claims 1 to 7.
9. The low-density steel according to claim 8, characterized in that: The grain size of the equiaxed austenite grain structure of the low-density steel is 5 μm-80 μm.
10. The low-density steel according to claim 9, characterized in that: In the low-density steel, the mass content of Mn element is 25%-35%, the mass content of Al element is 7%-11%, the mass content of C element is 0.7%-1.0%, the mass content of Nb is 0.03%-0.1%, and the mass content of Ti is 0-0.1%.
11. A front anti-collision beam of a vehicle, characterized in that: The vehicle front anti-collision beam is prepared using the low-density steel as described in any one of claims 8 to 10.
12. A vehicle, characterized in that: The vehicle is manufactured using the low-density steel as described in any one of claims 8 to 10.
Citation Information
Cited By
Ultrahigh-strength steel hot rolling forming process applied to part preparation
CN121082770A